Molecular cloning and expression study of grb10 interacting gyf domain protein 2 (GIGYF2) gene in zebrafish development - Lee, Jong Chen (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Grb 10 Interacting GYF domain protein 2 (GIGYF2) is a member of the GYGYF family gene which interacts specifically with Growth Factor Receptor Bound Protein 10 (Grb 10). Recently, GIGYF2 is nominated as candidate gene which causes Parkinson’s disease (PD) as it falls within PARK11 locus. At present, the functional role of GIGYF2 remains unknown. By using a zebrafish model, this study was to clone and study the expression of GIGYF gene in various stages of the zebrafish including the somite stages where first dopaminergic (DA) neurons differentiate at about 18 hpf in zebrafish. Total RNAs were extracted from 4-cell stage until 5 day post fertilization (dpf) stage of the zebrafish. First strand cDNA synthesis was then constructed to perform RT-PCR. Through RT-PCR, the expression pattern for GIGYF2 had been established from 4-cell until 5 dpf. The expression of GIGYF2 in 9 hpf, 18 hpf and 120 hpf are important for PD study as they may provide a hint into GIGYF2’s role in governing and regulating the dopaminergic differentiation and degeneration, which perhaps related to the onset of PD.